PERTUNJUKAN SOLIS TRUMPET DENGAN REPERTOAR ‘CONCERTO IN Eb MAJOR 2 MOVEMENT (ALLEGRO & ANDANTE)’, ‘PENAWAR RINDU’, DAN ‘CHERRY PINK AND APPLE BLOSSOM WHITE’ - Sayyidul Makruf; Selvi Kasman; Yon Hendri; Ferry Herdianto (Musica: Journal of Music, 2026)
This trumpet solo recital presents three repertoires from different musical genres: Concerto in E-flat Major (Classical) by Haydn, Penawar Rindu (Malay), and Cherry Pink and Apple Blossom White (Popular). This performance aims to analyze the musical characteristics of each repertoire and to interpret them within a trumpet solo performance through the application of genre-specific trumpet techniques. Conceptually, the recital is grounded in the paradigm of practice-based research, in which the performance process is understood as a form of artistic inquiry that generates new knowledge through musical action. The technical foundation of the performance is supported by specially designed etude exercises to address the specific technical challenges of each repertoire, combined with an in-depth interpretative approach. The results demonstrate that through this method, the distinctive characteristics of each genre can be effectively realized within a unified performance framework, highlighting the flexibility and artistic depth of a trumpet soloist.